The Impact of Current Ratio and Asset Composition on The Capital Structure of PT. Mustika Ratu Tbk - Isabela, Elisa; Hernawati, Euis (International Journal of Management and Business, 2025)
This research aims to examine the influence of the current ratio and asset composition on the capital structure of PT. Mustika Ratu Tbk during the timeframe from 2019 to 2023. This research employs a quantitative approach, specifically utilizing multiple linear regression analysis. This research utilized secondary data sourced from the annual reports of PT. Mustika Ratu Tbk, which has been publicly listed on the IDX from 2019 to 2023. The research data was collected via documentation methods, employing the resources available on www.idx.co.id and the official website of PT. Mustika Ratu Tbk. The findings of this study indicate that the current ratio variable does not influence the capital structure of PT. Mustika Ratu Tbk; the analysis demonstrates that the current ratio level has no significant effect on the capital structure. The asset structure variable positively influences the capital structure of PT. Mustika Ratu Tbk, indicating that an increase in the asset structure value leads to an enhancement in the capital structure. Consequently, neither the current ratio nor the asset composition exerts an influence on the capital structure of PT. Mustika Ratu Tbk. Therefore, it is prudent for investors to consider supplementary indicators beyond the current ratio and asset structure that may contribute to the enhancement of long-term profitability